The numerical simulation of the wing kinematics effects on near wake topology and aerodynamic performance in hovering Drosophila flight - Erzincanli, Belkis; Sahin, Mehmet (Elsevier BV, 2015)
zbMATH Open Web Interface contents unavailable due to conflicting licenses.
Keywords: insect flight; wing kinematics; near wake structure; ALE methods; Biopropulsion in water and in air; Biophysics; large-scale computations; Finite volume methods applied to problems in fluid mechanics; Computational methods for problems pertaining to biology; unstructured finite volume